Oxytocin as Treatment for Social Cognition, Not There Yet - Erdozain, Amaia M.; Peñagarikano, Olga (Frontiers in Psychiatry, 2020)
In a short time, oxytocin has progressed from being a regular hormone involved in parturition and breastfeeding to be possibly the neuromodulator that has gathered the most attention. Attributed many positive roles in the modulation of different aspects of social behavior, such as bonding, empathy, cooperation, trust, and generosity, as well as roles as a natural anxiolytic and antidepressant, the expectations on oxytocin becoming a treatment for a number of disorders with associated social deficits have dramatically raised over the last years. However, despite the field has been investigating oxytocin’s role in social behavior for over twenty years, there are still many unknowns on oxytocin’s mechanisms of action and efficiency and the increasing number of clinical trials administering oxytocin to different clinical groups seem to disagree in its properties and report in most cases conflicting results. This has led to some disappointment among researchers and clinicians as oxytocin might not be the miraculous molecule that works in a “one size fits all” fashion initially considered. Conversely, this down-side of oxytocin might merely reflect the complexity of its neurotransmission system. The current reality is that, although oxytocin seems to have potential therapeutic value, there are key questions that remain unanswered as to decide the optimal target groups and treatment course. Here, we present an overview on critical points regarding the oxytocin system in health and disease that need to be better understood to establish its therapeutic properties and to decide who could benefit the most from its treatment.